2014
DOI: 10.1186/1471-2431-14-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of red cell distribution width in identification of children aged 1-3 years with iron deficiency anemia against traditional hematological markers

Abstract: BackgroundCurrent strategy to identify iron deficiency anemia relies on markers involving high costs. Reports have suggested red cell distribution width (RDW) as a potential screening test for identifying iron deficiency anemia (IDA) but studies in pediatric populations are lacking. Our study elucidates the discriminative ability of RDW for detecting IDA among young children.Methods2091 blood reports of children aged 1–3 years from an urban low socio-economic population of Delhi were analyzed to evaluate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
5
42
0
2
Order By: Relevance
“…Blood films were reviewed manually to visually confirm automated differential counts and exclude gross morphological abnormalities. A Mentzer index (MCV/RBC) [10][11][12] was calculated for each participant. Dual-platform absolute lymphocyte subset counts and percentages were prepared using the Becton Dickinson FACSLyse/wash method (BDIS, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood films were reviewed manually to visually confirm automated differential counts and exclude gross morphological abnormalities. A Mentzer index (MCV/RBC) [10][11][12] was calculated for each participant. Dual-platform absolute lymphocyte subset counts and percentages were prepared using the Becton Dickinson FACSLyse/wash method (BDIS, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Although iron deficiency and other metabolic disorders, including vitamin B 12 and folate deficiencies, were not formally excluded in this cohort, haematological indices and the Mentzer index calculation were assessed. [10] Iron deficiency was suspected if a concurrent Hb <10 g/ dL, RDW >15% [11] and Mentzer index >13 [10,12] was found. As noted in another local adult reference interval study, [14] the findings suggested that 14.2% (54/381) of the children tested in this study had possible iron deficiency (Table 3).…”
Section: Rbc Parametersmentioning
confidence: 99%
“…Meanwhile, it can be lowered in patients with malnutrition due to hypoproteinemia. 10,25 In our study, despite being within normal limits, transferrin was significantly higher in the MA group than controls (p <0.001). MA group didn't have hypoproteinemia (total protein level: 6.6 ± 0.73 g/dL) and transferrin levels were able to identify IDA.…”
mentioning
confidence: 63%
“…Fe, TIBC, ferritin and transferrin are acute phase reactants that can be elevated depending on the presence of co-existing infectious or inflammatory processes. [8][9][10][11][12] Increased number of studies investigated the utility of sTfR in differentiating anemia in children. [13][14][15][16] sTfR is a truncated extracellular form of the transmembrane transferrin receptor (a glycoprotein primarily expressed in cells requiring iron) produced by proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…El Fe, la CTFH, la ferritina y la transferrina son proteínas de la fase aguda que pueden estar elevadas en presencia de procesos infecciosos o inflamatorios concurrentes. [8][9][10][11][12] …”
unclassified